Fixation shifts in a novel “no-report” binocular rivalry paradigm induce saccade-related perceptual switches - Kingir, Ege; Segawa, Ryo; Hesse, Janis K.; Kagan, Igor; Wilke, Melanie (Consciousness and cognition, 2025)
•Saccades in a novel no-report binocular rivalry paradigm induce perceptual switches.•Visual stimulation due to fixation point shifts is less potent.•Trials can be made longer to increase the ratio of internally generated switches.•Internally generated switches can be extracted with the analyses we provide. No-report paradigms help to avoid report-related confounds in conscious perception studies. A novel no-report binocular rivalry paradigm by Hesse and Tsao (2020) tracks conscious content using eye position as subjects follow fixation points linked to the rivaling stimuli. However, it remains unclear whether perceptual switches arise spontaneously or are induced by external factors such as visual transients due to fixation point shifts and saccades. We found an increased probability of perceptual switches time-locked to fixation point shifts, indicating that some switches are externally driven. To disentangle the effects of visual changes and saccades, we implemented a two-factorial design and found that saccades play a larger role in eliciting perceptual switches. We estimate that 14% of saccades trigger a switch, accounting for 24% of all perceptual transitions. Our findings provide an analysis framework and guidelines for excluding externally driven perceptual switches, enabling a clearer focus on internally generated perceptual dynamics.